Model construction for field operation machinery selection and configuration in wheat-maize double cropping system - Zhang, Fu; Chen, Tianhua; Teng, Shuai; Wang, Jiajia; Xu, Ruiliang; Guo, Zhijun (International Journal of Agricultural and Biological Engineering, 2021)
In order to scientifically and reasonably select the field operation machinery in wheat-maize double cropping system, first, the selection evaluation index system was constructed through the existing national standards and industry standards. Then the selection evaluation model was established based on the improved fuzzy comprehensive evaluation method. And the method of subjective weight and objective weight was used to overcome the drawbacks of the previous single weighting method that could not take into account the subject and object information of each indicator, and the weight value of each index was obtained in the evaluation system. Finally, the tillage process was used as an example, the field experiment was carried out to obtain the evaluation index value, and the model of selection evaluation was verified. The selection results of moldboard plough and rotary cultivator were as follows: the order of the comprehensive evaluation results of the moldboard plough results was ranked from high to low as 1LFK-435 (IIM), 1LFK-535 (IM), 1LF-342 (IIIM), 1LFT-445 (IVM), 1LFT-545 (VM), and the best machine type of the moldboard plough was IIM; the order of the comprehensive evaluation results of the rotary cultivator was ranked from high to low as 1GQKGN-240 (IIIR), 1GKNSM-250 (IVR), 1GKN-230K (IR), 1GKN-250K (IIR), 1GQKGN-220 (VR), and the optimal model of the rotary cultivator was IIIR. The experimental results showed that the results obtained by the evaluation model were in agreement with the local actual situation. The evaluation model will provide a scientific method for the selection of wheat and maize double cropping field operation machinery.Keywords: wheat-maize double cropping system, agricultural machinery, parts selection mode, evaluation system, fuzzy comprehensive evaluation method, combination weightDOI: 10.25165/j.ijabe.20211404.6383Citation: Zhang F, Chen T H, Teng S, Wang J J, Xu R L, Guo Z J. Model construction for field operation machinery selection and configuration in wheat-maize double cropping system. Int J Agric & Biol Eng, 2021; 14(4): 82–89.